Single Oral Dose of Fosfomycin Trometamol versus Ciprofloxacin for UTI prophylaxis in Invasive Urodynamics: A Prospective Randomized Double Blind Clinical Trial - Hisham A. Mosli; Hasan M.A. Farsi; Taha A. Abdulmagied; Abdulmalik M.S. Tayib; Ahmed J. Al-Sayyad; M. Mamdoh Rezk; Adel K. Altwarigi; M. Hani Abdulwahab (Journal of King Abdulaziz University: Medical Sciences, 2023)
The aim is to test the efficacy of a single oral dose of fosfomycin trometamol in preventing urinary tract infection as compared to ciprofloxacin in patients undergoing invasive urodynamics studies. Patients were randomized into 2 groups: A and B. Group A: a random group of patients undergoing urodynamics studies received a single pre-procedure dose of fosfomycin trometamol 3 gms orally 3 hours before the study. Group B: a random group of patients received a single pre-procedure dose of 500 mg ciprofloxacin 3 hours before the study. A total of 65 patients enrolled in the study (45 females and 20 males); the age range from 10 to 75 years with a mean of 50.32 ± 13.5. There were 39 patients in group A and 26 patients in group B. The post-procedure urine analysis showed increased presence of WBCs in Group A (fosfomycin trometamol) compared to group B (ciprofloxacin). Post-procedure, the negative urine cultures were reduced from 59% to 20.5% for group A and comparably from 57.7% to 23.1% in group B. A single dose of both fosfomycin trometamol and ciprofloxacin were equally in-effective in the prophylaxis against UTI in patients undergoing urodynamics studies.